Upaya Perpustakaan Perguruan Tinggi dalam Mewujudkan Integritas Akademik - Kurnia Sholihah; Sri Sulastri (Pustabiblia: Journal of Library and Information Science, 2019)
Every unit in higher education institution have a responsibility to maintain their academic integrity. Being dishonest by claiming other people's work (plagiarism) in a scientific work, is a violation to academic integrity and may be punished according to State Law Act. 20 Year 2003 about National Education System. The Sanction is revocation of academic title, or worst, criminal law act. Library has a function, which is to disseminate the scientific works result, and it holds important role to maintain the originality of the content. The purpose of this paper is to examine the efforts that library can do to maintain the academic integrity with a literature study method. Library can do many things to maintain academic integrity, such as: contributing to ethic's team, integrating information literacy program into the curriculum, having a policy to prevent plagiarism, doing an anti plagiarism campaign, using a tools to detect plagiarism, and providing adequate references. Those ways have to be done continuously and being synergized with all the units, so that the academic integrity can be a culture for academic community